Relationship Play Online Games With Motivation Learning In Teens - Nurhalisa; Aszrul AB; Nurlina (Jurnal Life Birth, 2021)
The use of uncontrolled games in adolescents can affect the learning process in school, especially the interest or desire to learn teenagers become reduced or can even disappear, this can certainly interfere with the child's education in the future. The decrease in students' desire to learn seriously can be influenced by the motivation of the student itself, namely the motivation of the student. The purpose of this study is to find out the relationship of playing online games with learning motivation in the youth of SMPN 41 Bulukumba students. This study uses an analytical observational research design with a "cross-sectional" approach. The sample of this study as many as 47 respondents were taken by purposive sampling method. Analysis of the data in this study using statistical tests Kolmogorov Smirnov. The results of the analysis used a statistical test Kolmogorov Smirnov with a confidence level (Î±=0.05). Based on the results of this test, the p-value was 0.019, thus p < Î± (0.019 < 0.05), then Ho was rejected and Ha received with a correlation value of r = - 0.420. The conclusion of this study is that there is a relationship between playing online games and learning motivation in adolescent students of SMPN 41 Bulukumba who are not in the direction of moderate correlation strength with a value of r = -0.420. Researchers suggest that the results of this study can be used as learning for students in order to divide time well between playing games with learning. In addition, further researchers also expected additional variables that may also affect many things in this study and also the addition of the number of research samples.